2012
DOI: 10.2478/v10201-011-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Castleman's Disease Mimicking Carotid Body Tumor

Abstract: A b s t r a c tThe authors present a case of 41-year-old patient with unicentric type of Castleman's disease in the neck imitating carotid glomus tumor. This rare condition can affect any lymph-node in the body and neck localization occurs only in 14% of cases. The case when Castleman's disease simulating chemodectoma have not been described yet in the literature. The authors give details on the course of the disease, its diagnosis and treatment and the discussion focuses on the reasons why the auxiliary imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Hanzel et al . [ 7 ] made a diagnosis of carotid body chemodectoma in their patient and discovered the Castleman's disease only during the histopathologic examination, as is the situation with most of these cases. In our case, re-review of the angiogram revealed features that in hindsight were atypical for carotid body tumors and hinted at a different pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Hanzel et al . [ 7 ] made a diagnosis of carotid body chemodectoma in their patient and discovered the Castleman's disease only during the histopathologic examination, as is the situation with most of these cases. In our case, re-review of the angiogram revealed features that in hindsight were atypical for carotid body tumors and hinted at a different pathology.…”
Section: Discussionmentioning
confidence: 99%